Revitalizing the Islamic Economy through Local Wisdom: A Systematic Literature Review on Minangkabau Matrilineal Legacy and Modern Sharia Interventions - Alimin Alimin; Desmadi Saharudin; Abhanda Amra; Irwan Irwan; Rizal Fahlefi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Despite Minangkabau women's nominal customary authority over ancestral property (harta pusako), poverty among female-headed households remains persistently high, and formal Islamic banking access continues to skew male — a paradox that anchors the novelty of this study. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this article synthesizes 42 peer-reviewed articles published between 2016 and 2025 to examine how Minangkabau's matrilineal legacy and cultural traces can revitalize the Islamic economy through local wisdom and modern sharia interventions. Thematic synthesis classifies the literature into three frameworks: Cultural-Institutional (n=19), Socio-Economic Empowerment (n=14), and Digital-Sustainability Integration (n=9). Digital transformation and environmental sustainability emerge as strikingly under-explored themes within matrilineal Islamic economic research, representing a critical novelty gap. Theoretically, the study extends the Resource-Based View and proposes a feminist reading of Maqasid al-Shariah. Practically, it recommends aligning zakat and waqf with matrilineal inheritance practices, developing culturally embedded fintech, and piloting green sukuk. Future research should pursue comparative studies across matrilineal societies, longitudinal mixed-methods designs, blockchain-based waqf prototyping, and policy experiments linking Islamic finance to sustainability goals